(untitled) (Research, Society and Development, 2021)
The purpose of this study was to carry out the translation and cross-cultural adaptation of the Dental Patient Feedback on Consultation (DPFC) questionnaire into the Portuguese language and considering the Brazilian cultural context. For the translation and cross-cultural adaptation processes, international guidelines proposed in the literature were followed: authorization of the questionnaire’s authors, translation of the questionnaire into Brazilian Portuguese by two independent professionals, agreement between the two versions of the translation, back-translation into English and evaluation by the expert committee. The preliminary version of the questionnaire was answered by users of Basic Health Units located in Belém, Pará, in order to assess the understanding of the questionnaire items. The two initial translations did not present any significant discrepancies, which facilitated the synthesis in a single version. The expert committee reviewed all translations and reached consensus on the preliminary version of the questionnaire. From the responses of the study participants regarding the understanding of the questionnaire, changes were made to items 5 and 7. The understanding of the questionnaire items by the participants increased substantially after the modifications. The Brazilian version of the Dental Patient Feedback on Consultation questionnaire demonstrated equivalence with the meanings of the original instrument. The questionnaire was well accepted and understood by the participants, demonstrating its suitability for the Brazilian population.